Criminal legal penalties, substance use, and overdose: a concept mapping study examining Colorado’s criminal legal penalties - Katherine LeMasters; Samantha K. Nall; Cole Jurecka; Betsy Craft; Paul J. Christine; Ryan Goodman; Jessie Henderson; Robert Haywood-James; Angela Williams; Grace Wittner; Joshua A. Barocas (BMC Global and Public Health)
Abstract Background In the USA, many states, including Colorado, have increased criminal penalties for illicit opioid possession, which may alter overdose risk. We aimed to evaluate the relationship between Colorado’s increased drug-related criminal legal penalties, risk of overdose, and substance use patterns. Methods We used concept mapping — a mixed-methods approach used to develop a conceptual understanding of an issue from a community lens — to engage with people with living and/or lived experience with the criminal legal system, substance use, and/or overdose, their loved ones, and service providers. In facilitated discussion, we used the prompt: “Do you see overdose and substance use, in Colorado, being impacted by an individual's involvement with the criminal legal system?” Participants — recruited from community-based organizations — identified, rated, sorted, and categorized factors affecting criminal legal involvement, substance use, and/or overdose in their community. We used groupwisdom to develop concept maps and to analyze findings. Results Twenty-four individuals (ages 18–70) participated; most had living and/or lived experience. Participants identified 100 distinct factors, which were sorted into 9 clusters: societal impacts of criminal legal involvement, lifesaving benefits to decreased criminal legal penalties, environmental barriers of criminal legal involvement, structural barriers to recovery services, essential culturally aware community-based services, strategic allocation of funding, strategies to improve law enforcement’s impact, changing policies to keep law enforcement accountable and better educate law enforcement on community culture, and community issues with law enforcement to prioritize. Of the 40 most influential and common factors, most related to structural impacts of criminal legal involvement and barriers to recovery (e.g., long waitlists, job loss). Conclusions Using concept mapping, we worked with community members to identify and prioritize factors associated with substance use and overdose amidst increasing drug-related criminal legal penalties. These insights (e.g., law enforcement’s role should be acting as a bridge to mental health and recovery services) are critical for policymakers and service providers, as they speak to the need for investing in re-entry services, harm reduction services, and co-responder models for behavioral health crises.